Clinical impact of statin intensity according to age in patients with acute myocardial infarction - Kyusup Lee; Myunhee Lee; Dae-Won Kim; Jinseob Kim; Sungmin Lim; Eun Ho Choo; Chan Joon Kim; Chul Soo Park; Hee Yeol Kim; Ki-Dong Yoo; Doo Soo Jeon; Kiyuk Chang; et al. (PLoS ONE, 2022)
Background The available data are not sufficient to understand the clinical impact of statin intensity in elderly patients who undergo percutaneous coronary intervention (PCI) due to acute myocardial infarction (AMI). Methods Using the COREA-AMI registry, we sought to compare the clinical impact of high- versus low-to-moderate-intensity statin in younger (<75 years old) and elderly (≥75 years old) patients. Of 10,719 patients, we included 8,096 patients treated with drug-eluting stents. All patients were classified into high-intensity versus low-to-moderate-intensity statin group according to statin type and dose at discharge. The primary end point was target-vessel failure (TVF), a composite of cardiovascular death, target-vessel MI, or target-lesion revascularization (TLR) from 1 month to 12 months after index PCI. Results In younger patients, high-intensity statin showed the better clinical outcomes than low-to-moderate-intensity statin (TVF: 79 [5.4%] vs. 329 [6.8%], adjusted hazard ratio [aHR] 0.76; 95% confidence interval [CI] 0.59–0.99; P = 0.038). However, in elderly patients, the incidence rates of the adverse clinical outcomes were similar between two statin-intensity groups (TVF: 38 [11.4%] vs. 131 [10.6%], aHR 1.1; 95% CI 0.76–1.59; P = 0.63). Conclusions In this AMI cohort underwent PCI, high-intensity statin showed the better 1-year clinical outcomes than low-to-moderate-intensity statin in younger patients. Meanwhile, the incidence rates of adverse clinical events between high- and low-to-moderate-intensity statin were not statistically different in elderly patients. Further randomized study with large elderly population is warranted.